The Media's Portrayal of Radical Islam (International Journal of Innovative Research in Engineering & Management, 2023)
This same impact of social internet on  bigotry is modern society is an attractive research area. It  deals with news prejudice, so it's crucial to look at where  the television promotes to discrimination in specific ways.  Because White persons controlled contemporary gaming  industry and chose the images of Black individuals to  convey throughout the beginning stages of tv and film,  African Americans battled to express your own stories,  beliefs, views, even selves. Our study incorporated  comprehensive understanding of Bandura's Observational  Learning in order to know how advertisements affect our  beliefs and values. This study looked for when resources  are available to mass media viewers, as well as how the  relevant organization our attitudes, sentiments, and  behaviors towards everyone else. In particular, as it relates  to racial inequities, biases, racial implicit bias, and African  American men's perspectives. Occasions and evidence on  perceived discrimination, as well as their impact on press  attention, have been discovered in major findings. The  representation of Muhammad and Muslims as in British  press is examined in this article. It suggests that British  Muslims are frequently portrayed as an "alien other." It  claims that this misperception is linked to that same  emergence of something like a 'racist,' particularly  Xenophobia, which has its roots in social portrayals of the  'everyone else.' To support this claim, the article provides  a synopsis of just how racial groups have really been  depicted there in British newspaper, arguing that portrayals  of British Muslims in Religion are based on comparable  ideas of 'deviations' and 'Notre.'
Keywords: Islam; Islamophobia; Media; Racial; Racism